An Enzyme-Linked Immunosorbent Assay for Urokinase-Type Plasminogen Activator (u-PA) and Mutants and Chimeras Containing the Serine Protease Domain of u-PA - Declerck, Paul J; Van Keer, Leen; Verstreken, Maria; Collen, Désiré (Thrombosis and Haemostasis, 1992)
An enzyme-linked immunosorbent assay (ELISA) for quantitation of natural and recombinant plasminogen activators containing the serine protease domain (B-chain) of urokinase-type plasminogen activator (u-PA) was developed, based on two murine monoclonal antibodies, MA-4D1E8 and MA-2L3, raised against u-PA and reacting with non-overlapping epitopes in the B-chain. MA-4D1E8 was coated on microtiter plates and bound antigen was quantitated with MA-2L3 conjugated with horseradish peroxidase. The intra-assay, inter-assay and inter-dilution coefficients of variation of the assay were 6%, 15% and 9%, respectively. Using recombinant single-chain u-PA (rscu-PA) as a standard, the u-PA-related antigen level in normal human plasma was 1.4 ± 0.6 ng/ml (mean ± SD, n = 27).The ELISA recognized the following compounds with comparable sensitivity: intact scu-PA (amino acids, AA, 1 to 411), scu-PA-32k (AA 144 to 411), a truncated (thrombin-derived) scu-PA comprising A A 157 to 411, and chimeric t-PA/u-PA molecules including t-PA(AA1-263)/scu-PA(AA144-411), t-PA(AA1-274)/scu-PA(AA138-411) and t-PA(AA87-274)/scu-PA(AA138-411). Conversion of single-chain to two-chain forms of u-PA or inhibition of active two-chain forms with plasminogen activator inhibitor-1 or with the active site serine inhibitor phenyl-methyl-sulfonyl fluoride, did not alter the reactivity in the assay. In contrast, inactivation with α2-antiplasmin or with the active site histidine inhibitor Glu-Gly-Arg-CH2Cl resulted in a 3- to 5-fold reduction of the reactivity. When purified scu-PA-32k was added to pooled normal human plasma at final concentrations ranging from 20 to 1,000 ng/ml, recoveries in the ELISA were between 84 and 110%.The assay was successfully applied for the quantitation of pharmacological levels of scu-PA and t-PA(AA87_274)/scu-PA(AA138-411) in plasma during experimental thrombolysis in baboons.Thus the present ELISA, which is specifically dependent on the presence of the serine protease part of u-PA, is useful for measurement of a wide variety of variants and chimeras of u-PA which are presently being developed for improved thrombolytic therapy.